Ontology‐based employer demand management. (6th April 2015) - Terblanche, Chamonix; Wongthongtham, Pornpit
Summary: Skills shortages globally pose a real and urgent need for proper investigation and workforce development planning into the future. Analysing workforce development and employer demand needs through electronic job market allows much deeper and wider research into skill shortages. Current methods do not provide the level of depth required to address such important economic implications. In this paper, we present a system aiming to gather and analyse current employer demand information from online job advertisements. It identifies current employer demand needs analysed from electronic job market. Copyright © 2015 John Wiley & Sons, Ltd.